Analysis Acceptance of Use Internet Banking and Mobile Banking, Case Study: Standart Application in XYZ Company - Iwang Aryadinata; Febriliyan Samopa (IPTEK Journal of Proceedings Series, 2019)
Financial Technology (Fintech) is a technology that connects financial sector and user. Fintech is solution for problem that exist in society that is user those who live far from city to be able access transact financially by making non-cash transactions. This non-cash transactions are important component in world economy and also one of the program that Bank Indonesia wants to improve. This study will be analysed what factors that influence customer behavior in acceptance of using Internet Banking and Mobile banking for transactions using the Technology Acceptance Model. In this study, the author takes a case study at standart Internet Banking and Mobile Banking developed by XYZ Company and the scope population of the sample collection is one of the Banks in Bandung that has used the application developed by XYZ Company. This research uses Partial Least Square Structural Equation Modeling (PLS-SEM) method in analyzing. The results obtained are the most significant factors on customer acceptance use of Internet Banking and Mobile Banking applications for transactions is the subjective norm, experience, result demonstrability, perceived enjoyment, computer playfulness, computer self-efficacy, perception of external control, perceived usefulness, perceived ease of use, behavioral intention, dan use behavior